Integrasi Media Sosial pada Pembelajaran Mata Kuliah Filsafat Pendidikan Islam - Faturrahman, Irwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study is to look at the effect of the integration of Social Media on student motivation in learning Islamic Philosophy courses. The research method used was quasi-experimental. the research design used is nonequivalent control group design. Observation was carried out twice namely before treatment and after treatment. The research was conducted at the Tarbiyah STAIN Curup Department, with two classes compared, namely class A as an experimental class (BKI Study Program with 13 students) and class B as a control class (MPI Study Program with 19 students). Data analysis techniques in this study used the Liliefors test to test data normality, Fisher's test to test data homogeneity, t-test to test hypotheses, and normal gain to determine differences in student learning motivation between the experimental class and the control class. The results of the calculation of hypothesis testing obtained t-test of 3.2 with a t-table price of 2.08, then t-count> t-table. Conclusion, there is an influence of learning of Islamic Education Philosophy courses integrated with social media on increasing student motivation. Keywords: Social Media, Learning Motivation, Learning.